Genetic Diversity and Connectivity of Reef-Building Halimeda macroloba in the Indo-Pacific Region - Xiaohan Song; Jianting Yao; Michael Y. Roleda; Yanshuo Liang; Rui Xu; Yude Lin; Shienna Mae C. Gonzaga; Yuqun Du; Delin Duan (Plants)
Understanding population genetic connectivity is crucial for the sustainability and persistence of marine biodiversity. As a fundamental reef-building macroalga of the coastal ecosystem, Halimeda macroloba Decaisne is one of the dominant intertidal seaweeds in the Indo-Pacific region. However, its genetic structure and population connectivity have been poorly recognized. Here, we explored the population genetic structure and genetic connectivity of H. macroloba using chloroplast tufA, rps3-rpl14, and rbcL. Our results indicated low genetic diversity and shallow population genetic structure at the intraspecific level, uncovering five genetic groups with six subdivided lineages in tufA and two genetic clusters in rps3-rpl14. We detected demographic expansion in the last glacial period of the Pleistocene and significantly asymmetric gene flow among different geographical units. We suggest that the southwestward ocean currents under the influence of northeast monsoon in the Indo-Pacific region are the main factor in shaping the present genetic structure, and the asexual reproduction of H. macroloba also plays an important role of the low genetic diversity pattern; in addition, the divergence between genetic clusters might be related to the historical isolation led by the paleoclimate oscillation in the Pleistocene. The Xisha Islands in the northern South China Sea might serve as a potential refugium of H. macroloba, which needs extra attention to conservation management. Given the limitation of sample size, we need to conduct more field work and carry out further research at a larger scale in the future. Our study provided new insights into the theory of population connectivity in the Indo-Pacific region and provided scientific basis for tropical costal seaweed conservation.